Kemampuan Berpikir Kreatif Siswa Sekolah Dasar dalam Menulis Puisi: Analisis Kualitatif Berdasarkan Indikator Fluency, Flexibility, Originality, dan Elaboration - M. Kamal Al Ibad; Rizka Novi Irmaningrum; Ari Susandi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Creative thinking is a 21st-century competency that needs to be fostered through Indonesian language instruction, particularly in poetry writing. However, observations indicate that students' creativity in writing poetry varies, especially regarding idea development, diction, and the crafting of poetic expressions. This study aims to analyze the creative thinking abilities of fifth-grade students in writing poetry and to identify the factors that facilitate or hinder this process. A descriptive qualitative approach was employed, involving 30 fifth-grade students selected via purposive sampling and the class teacher as a supporting informant. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model comprising data reduction, data display, and conclusion drawing with validity verified through source, technique, and time triangulation. The results show that students' creative thinking abilities have developed across the indicators of fluency, flexibility, originality, and elaboration, though not yet optimally for all students. Creativity is influenced by learning motivation, teacher support, the learning environment, and vocabulary mastery, whereas low self-confidence and limited experience act as inhibiting factors. These findings highlight the importance of implementing contextual, creative, and student-centered instruction to foster creative thinking skills in poetry writing at MI Muhammadiyah 4 Brangsi.